THE PROBLEMS OF PASSENGER TRANSPORTATIONS IN AN INTERNATIONAL COMMUNICATION - Barash, Yu. S.; Hayduk, N. O.; Drebot, Kh. V. (Science and Transport Progress, 2010)
The basic aspects of international passenger transportations in Ukraine are represented. The analysis of present situation in these transportations is carried out. Some variants of solving the problems of passenger transportations in an international communication are considered.